Study on Isolation of Lactic Acid Bacteria Fermented Vegetable Juice - MANYSOAT, Soutthanou; PHATTHANA, Ampy; YELEETHOR , Khamphone; PHOVISAY, Somsay (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study was aim to investigate the chemical composition and bacteria characteristics in fermented vegetable juice. The samples were collected from Chomphet district LuangPrabang province. Vegetable juices were prepared from three different age of vegetables T1 (ripen vegetables), T2 (fresh vegetables) and T3 (germ vegetables), all treatments submitted to measure pH, determined the amount of Lactic acid content, isolated and characterization of lactic acid bacteria including population of lactic acid bacteria and morphology observation. The results showed pH of T1 and T2 were 4.60 and 4.50 respectively which significantly higher than T3 (3.58), (p<0.05), total acid content of T1, T2 and T3 were 7.83, 8.09 and 13.19 g/L (as lactic acid) respectively (p<0.05). The properties of microbial fund that T1, T2 and T3 consist of 7.38, 7.90, and 8.90 Log CFU/ mL of Lactic acid bacteria (p<0.05). after isolated the bacteria that involve of lactic acid production found that T1 consists 1 isolate, T2, 2 isolates and T3 also 2 isolates, totally 5 isolates, additionally all 5 isolates were stained with gram positive bacteria with rod-sharp colony and slightly curve, suggested that they were Lactobacillus bacteria